Continuous Renal Replacement Therapy (CRRT) in Critically Ill Children with Multiple Organ Dysfunction Syndromes: A Case Report (Bangladesh Journal of Child Health, 2022)
Acute kidney injury (AKI) is a serious and potentially fatal clinical consequence of disease that increases morbidity and mortality in hospitalized children. In the event of AKI and fluid overload, renal replacement therapy (RRT) is a must-have therapy. In critically sick children with multi organ dysfunction syndrome (MODS) who are hemodynamically unstable, CRRT (continuous renal replacement therapy) is the cornerstone of dialysis. Although several hospitals in the country have begun to utilize CRRT in adult patients in the critical care unit, a lack of expertise and high therapeutic costs have prevented widespread adoption of CRRT. We managed a child with CRRT, who had AKI and MODS as a consequence of dengue shock syndrome and also was hemodynamically unstable in our hospital. The child’s renal function improved as a result of the CRRT therapy, as did his MODS. We have summarized our experience using CRRT in children for the first time in Bangladesh in this article.BANGLADESH J CHILD HEALTH 2021; VOL 45 (2) : 120-123